2002
DOI: 10.1083/jcb.200105051
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of substrate adhesion dynamics via microtubule targeting requires kinesin-1

Abstract: Recent studies have shown that the targeting of substrate adhesions by microtubules promotes adhesion site disassembly (Kaverina, I., O. Krylyshkina, and J.V. Small. 1999. J. Cell Biol. 146:1033–1043). It was accordingly suggested that microtubules serve to convey a signal to adhesion sites to modulate their turnover. Because microtubule motors would be the most likely candidates for effecting signal transmission, we have investigated the consequence of blocking microtubule motor activity on adhesion site dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
101
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 58 publications
(102 reference statements)
9
101
0
Order By: Relevance
“…56 Recently, kinesin has shown to be required for the focal delivery of possible components to retard substrate adhesions' growth or promote their disassembly. 57 In the present study, amf/phi-transfected cells showing high motility exhibited not only augmented expression of KIF3A but also a tendency of distribution shift to the cell periphery. KIF3A may play an important role in the focal delivery of a component(s) that modulates the dynamics of adhesive structures at the focal contact, and then stimulate cell motility.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…56 Recently, kinesin has shown to be required for the focal delivery of possible components to retard substrate adhesions' growth or promote their disassembly. 57 In the present study, amf/phi-transfected cells showing high motility exhibited not only augmented expression of KIF3A but also a tendency of distribution shift to the cell periphery. KIF3A may play an important role in the focal delivery of a component(s) that modulates the dynamics of adhesive structures at the focal contact, and then stimulate cell motility.…”
Section: Discussionsupporting
confidence: 55%
“…30 These molecules corresponded well with components that are possible molecules specifically accumulated at microtubule tips as cofactors, together with cargo delivered by kinesin, in signal transduction events. 57 Small GTPase rho and the downstream effecter molecules may be possible components to which KIF3A may be related, delivering to the cell periphery in association with microtubules in AMF/PHI-stimulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Time lapse imaging studies indicated that growing microtubules target focal adhesions for subsequent disassembly [133,136]. A single focal adhesion may be targeted multiple times and a single microtubule tip may target multiple focal adhesions suggesting dynamic interaction of microtubule and actin filament systems and their associated molecular motors [136,137]. Consistent with this view, inhibiting the kinesin motors (predominantly plus-end directed motors of the microtubule system) can interfere with focal adhesion disassembly without affecting microtubule dynamics or targeting to focal adhesions [137,138].…”
Section: Microtubule and Endocytic Regulation Of Focal Adhesionsmentioning
confidence: 86%
“…A single focal adhesion may be targeted multiple times and a single microtubule tip may target multiple focal adhesions suggesting dynamic interaction of microtubule and actin filament systems and their associated molecular motors [136,137]. Consistent with this view, inhibiting the kinesin motors (predominantly plus-end directed motors of the microtubule system) can interfere with focal adhesion disassembly without affecting microtubule dynamics or targeting to focal adhesions [137,138]. Thus, microtubules may direct kinesin motors bound to disassembly factors to focal sites to promote adhesion turn over.…”
Section: Microtubule and Endocytic Regulation Of Focal Adhesionsmentioning
confidence: 99%
See 1 more Smart Citation